Is social capital part of the institutions continuum? - Stephen Knowles (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2005)
Social capital is generally interpreted as the degree of trust, co-operative norms and networks and associations within a society. Economists have become increasingly interested in social capital, following the seminal work of Coleman (1988) and Putnam (1993). Since the publication of these studies a vast quantity of research on social capital has been published by economists, as well as researchers from other academic disciplines. This paper argues that in terms of its definition, and the arguments advanced as to why social capital is likely to affect economic performance, social capital is a very similar concept to what North (1990) defined as informal institutions. This suggests that social capital can be empirically modelled as a deep determinant of economic development.
Keywords: Z13; O11; 330; Social capital; institutions